2022
DOI: 10.1002/ajim.23330
|View full text |Cite
|
Sign up to set email alerts
|

Estimating mortality from coal workers' pneumoconiosis among Medicare beneficiaries with pneumoconiosis using binary regressions for spatially sparse data

Abstract: Background: Coal workers' pneumoconiosis (CWP) is an occupational lung disease due to inhalation of coal dust. We estimated mortality from CWP and other pneumoconioses among Medicare beneficiaries.Methods: We used the 5% Medicare Limited Claims Data Set, 2011-2014, to identify patients diagnosed with ICD-9-CM 500 (CWP) through 505 (Asbestosis, Pneumoconiosis due to other silica or silicates, Pneumoconiosis due to other inorganic dust, Pneumonopathy due to inhalation of other dust, and Pneumoconiosis, unspecifi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 29 publications
(73 reference statements)
0
2
0
Order By: Relevance
“…Comprehensive research conducted across the USA underscores that the prevalence of CWP and its most advanced manifestation, PMF, is notably higher in mines situated in the central Appalachian region. This conclusion is supported by data derived from the federal black lung program and the national surveillance database [31][32][33][34].…”
Section: Rcmd Sources and Exposure In Coal Minesmentioning
confidence: 70%
“…Comprehensive research conducted across the USA underscores that the prevalence of CWP and its most advanced manifestation, PMF, is notably higher in mines situated in the central Appalachian region. This conclusion is supported by data derived from the federal black lung program and the national surveillance database [31][32][33][34].…”
Section: Rcmd Sources and Exposure In Coal Minesmentioning
confidence: 70%
“…The prevalence of CAD among PCN has been presented by Paul et al, who collected information from 8531 patients with PCN from the 5% Medicare Claims Limited Data Set in the United States between 2011 and 2014 [ 5 ]. They reported that CAD occurred in 13.9% of all patients with PCN and accounted for 18.7% of those who lost their lives.…”
Section: Discussionmentioning
confidence: 99%
“…Various kinds of mineral dust could cause various respiratory and cardiovascular diseases. PCN is associated with poor prognosis from these diseases [ 3 , 4 , 5 ].…”
Section: Introductionmentioning
confidence: 99%